2010
DOI: 10.4297/najms.2010.2444
|View full text |Cite
|
Sign up to set email alerts
|

The multi-systemic nature of diabetes mellitus: Genotype or phenotype?

Abstract: Background:This article discusses factors which materially influence the diagnosis, prevention and treatment of diabetes mellitus but which may be overlooked by the prevailing biomedical paradigm. That cognition can be mathematically linked to the function of the autonomic nervous system and physiological systems casts new light upon the mechanisms responsible for homeostasis and origins of disease. In particular, it highlights the limitations of the reductionist biomedical approach which considers mainly the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 116 publications
(97 reference statements)
0
27
0
Order By: Relevance
“…Grakov's Strannik technology performs two fundamental functions: (i) as a screening technology [9] which is able to determine the onset and progression of pathologies in all main organs (typically 15 pathologies per organ in the 30 main organs), each pathology being defined in terms of its genotype and its phenotype [10]; and (ii) to treat the most destabilised physiological system thereby reestablishing optimum autonomic stability and homeostasis [11]. Such a technology is an extraordinary development which initial research has indicated appears to be more advanced than any current technology(s) [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Grakov's Strannik technology performs two fundamental functions: (i) as a screening technology [9] which is able to determine the onset and progression of pathologies in all main organs (typically 15 pathologies per organ in the 30 main organs), each pathology being defined in terms of its genotype and its phenotype [10]; and (ii) to treat the most destabilised physiological system thereby reestablishing optimum autonomic stability and homeostasis [11]. Such a technology is an extraordinary development which initial research has indicated appears to be more advanced than any current technology(s) [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Both the genetic and phenotypic processes which influence pathological onset or progression have to be quantified [2,3]. This is immensely significant when diagnosing diabetes.…”
Section: E Most Medical Tests Consider Only a Portion Of A Normalmentioning
confidence: 99%
“…In most patients diabetes presents as a combination of genotype and phenotype influencing the function of the cells of the islets of Langerhans [2,3]. This occurs because the genetic expression of proteins (in this case insulin)…”
Section: Dmentioning
confidence: 99%
“…In order to understand the issue in greater detail we must consider (i) the fundamental relationship between genotype (protein expression) and the wider influence of environmental factors i.e. non-genetic or phenotype [27] and, (ii) the mechanisms which the brain uses to regulate the body's function [28] and vice versa ( Figure 1). …”
Section: The Relationship Between Sensory Input and Biological Inputmentioning
confidence: 99%